2014
DOI: 10.1120/jacmp.v15i4.4847
|View full text |Cite
|
Sign up to set email alerts
|

Validation of nonrigid registration in pretreatment and follow‐up PET/CT scans for quantification of tumor residue in lung cancer patients

Abstract: Nonrigid registrations of pre‐ and postradiotherapy (RT) PET/CT scans of NSCLC patients were performed with different algorithms and validated tracking internal landmarks. Dice overlap ratios (DR) of high FDG‐uptake areas in registered PET/CT scans were then calculated to study patterns of relapse. For 22 patients, pre‐ and post‐RT PET/CT scans were registered first rigidly and then nonrigidly. For three patients, two types (based on Demons or Morphons) of nonrigid registration algorithms each with four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Non-rigid registration was based on the Morphons algorithm using eight resolution steps of 10 iterations with a Gaussian smoothing filters of 1.5 times the voxel dimensions [23]. The algorithm has been investigated for accuracy of tumor residue by Spijkerman et al [24]. For lung tissue registration this method had accuracy well below 5 mm resampling in which we have used in this study.…”
Section: Image Registration and Data Analysismentioning
confidence: 99%
“…Non-rigid registration was based on the Morphons algorithm using eight resolution steps of 10 iterations with a Gaussian smoothing filters of 1.5 times the voxel dimensions [23]. The algorithm has been investigated for accuracy of tumor residue by Spijkerman et al [24]. For lung tissue registration this method had accuracy well below 5 mm resampling in which we have used in this study.…”
Section: Image Registration and Data Analysismentioning
confidence: 99%
“…Aerts et al showed that the residual tumor volume after RT is mainly located within the pre-RT high FDG-uptake volume. However, 30% of the residual volume did not correspond to the high FDG volume (11, 13). This may be caused by tumor regrowth in pre-RT hypoxic tumor subvolumes located outside the high FDG volume.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, we tried to focus on landmarks around the tumour and areas of RILD, as, although these are the regions that are hardest to align, they are also the ones of most interest. In Spijkerman et al (2014), the best performing, medium, and worst performing groups had errors of 3.8 mm, 4.5 mm and 8.0 mm respectively. Once again, the temporal distance between scans was only about 4 months.…”
Section: Discussionmentioning
confidence: 95%